Stronger Risk Controls, Lower Risk: Evidence from U.S. Bank Holding Companies - ELLUL, ANDREW; YERRAMILLI, VIJAY (Journal of Finance, 2013)
ABSTRACT We construct a risk management index (RMI) to measure the strength and independence of the risk management function at bank holding companies (BHCs). The U.S. BHCs with higher RMI before the onset of the financial crisis have lower tail risk, lower nonperforming loans, and better operating and stock return performance during the financial crisis years. Over the period 1995 to 2010, BHCs with a higher lagged RMI have lower tail risk and higher return on assets, all else equal. Overall, these results suggest that a strong and independent risk management function can curtail tail risk exposures at banks.